Settler Education: Acknowledgement, Self-Location, and Settler Ethics in Teaching and Learning - Kouri, Scott (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
This paper begins with a critical exploration, from the location of a settler, of how land acknowledgements and practices of self-location function in child and youth care teaching and learning. I critically examine settler practices of acknowledgement, self-location, appropriation, consciousness-raising, and allyship. I use the concepts of settler ethics and responsibilities to underline the importance of accountability in child and youth care pedagogy. I argue that settlers have a responsibility to take action within the challenging ethical landscape of teaching and learning within the settler colonial context. My overall aim is to contribute to the critical and decolonizing literature in child and youth care from the location of a settler educator and child and youth care practitioner.